Pemetaan Kerentanan Degradasi Lingkungan Berbasis Environmental Criticality Index (ECI) di Kota Banjarmasin - Forjan Forjan; Andi Baso Sofyan A. P.; Ahmad Aris Mundir Sutaji; Siti Hutami Adianengsih Gaffar (Geomatics Technology Study Program, Politeknik Pertanian Negeri Samarinda, 2026)
This study was motivated by the rapid urbanization and land-use changes occurring in Banjarmasin City, which may contribute to environmental degradation. These changes are characterized by a reduction in vegetation cover and water bodies, as well as an increase in land surface temperature and the expansion of built-up areas. This study aims to map the level of environmental degradation vulnerability in Banjarmasin City in 2024 based on the Environmental Criticality Index (ECI) using remote sensing technology and Landsat 8 OLI/TIRS satellite imagery. The analysis was conducted using four parameters: land surface temperature, vegetation density, building density, and the water body index. The results indicate that the land surface temperature in Banjarmasin City in 2024 was dominated by the low-temperature class (15.1°C–22.1°C), covering 8,653 hectares or 87% of the total area, while the moderate to high-temperature class (22.2°C–33.0°C) covered 1,298 hectares or 13% of the total area. The vegetation density analysis revealed that most of the study area exhibited a moderate level of vegetation density, covering 5,530 hectares (56%). Meanwhile, building density was predominantly classified as low, encompassing 6,809 hectares (68%). Based on the water body index analysis, non-water areas dominated the city, covering 9,314 hectares (93.6%), whereas water bodies occupied only 637 hectares (6.4%). The classification of environmental degradation vulnerability based on the Environmental Criticality Index (ECI) showed that areas with low vulnerability covered 2,370 hectares (23.8%), areas with moderate vulnerability covered 4,539 hectares (45.0%), and areas with high vulnerability covered 3,042 hectares (30.6%) of the total area of Banjarmasin City.